2016
DOI: 10.1007/s10753-016-0351-1
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CD354 (TREM-1) Ameliorates Anti-GBM-Induced Nephritis

Abstract: CD354, Triggering Receptor of Myeloid Cells-1 (TREM-1), is a potent amplifier of myeloid immune responses. Our goal was to determine the expression and function of TREM-1 in immune-mediated nephritis. An anti-glomerular basement membrane antibody (anti-GBM)-induced nephritis model was employed, where mice were sensitized with rabbit IgG followed by anti-GBM serum to induce disease. Anti-GBM-treated 129x1/svJ mice developed severe nephritis whereas C57BL/6 (B6) mice were resistant to disease. Anti-GBM disease r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Lo TH et al found that in the ureteral obstruction mouse model, TREM-1 regulated the polarization of macrophages [6]. Du et al further indicated that TREM-1 has the therapeutic value in anti-GBM-induced nephritis [16]. The polarization of macrophages played a vital role in renal fibrosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Lo TH et al found that in the ureteral obstruction mouse model, TREM-1 regulated the polarization of macrophages [6]. Du et al further indicated that TREM-1 has the therapeutic value in anti-GBM-induced nephritis [16]. The polarization of macrophages played a vital role in renal fibrosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TREM-1 is readily detected in biological fluids of patients suffering from a variety of disease 11 . 19 .…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 can be expressed by the inflammatory infiltrate and renal epithelial cells in chronic disease 19 .…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the limited quantity of IgA1-containing immune complexes isolated from circulation, we did not have enough IgA1-containing immune complexes for further experiments. Secondly, it was reported that urinary sTREM-1 levels are higher in patients with other kidney diseases, such as anti-GBM disease and acute kidney injury [24,28]; thus, it could not be a specific biomarker for IgAN. More studies are needed to evaluate its potential clinical implications in these kidney diseases.…”
Section: Elevated Urinary Strem-1 Levels In Patients With Iganmentioning
confidence: 99%